RANCANG BANGUN SISTEM INFORMASI PENJUALAN DAN PEMESANAN CATERING PADA CATERING ZHAFIRAH JAMBI BERBASIS WEB: Information System, Marketing, Ordering, Catering, Laravel, PHP, MySQL - Wahyuning Astuti, Reny; Suana, Irma; Rifki, Muhammad (FORTECH (Journal of Information Technology), 2025)
Advances in information technology are encouraging businesses to utilize online media for marketing and ordering products and services. Catering Zhafirah Jambi capitalized on this opportunity by building a web-based marketing and ordering system to improve operational efficiency and simplify customer transactions. This system was developed using the Laravel framework, PHP programming language, and MySQL database, with key features including a menu catalog, order form, online payment, customer data management, and testimonials. System requirements included inputs in the form of user data, menus, orders, admin, and payment methods; processes such as registration, login, ordering, payment, menu management, orders, and reviews; and outputs in the form of sales reports, order confirmations, menu lists, and order statuses. Test results showed the system performed well, with an easy-to-use interface, and accelerated ordering and data management. This system is expected to improve customer service while expanding Catering Zhafirah Jambi's market reach.